Odpowiedzi

2009-10-18T13:59:02+02:00
6x-2(x-4)=8
6x-2x+8=8
4x=0 |:4
x=0

2-x =-¾
-x = -3/4 - 2
-x = -10/4 | * -1
x = 10/4
x = 2 1/2

(x-3)(x-3)-(x+2)²-5=x+4
x²-3x-3x+9-x²+4x+4-5=x+4 (x² się skracają)
-3x-3x+4x-x=4-9-4+5
-3x=-4 | :(-3)
x = 1 1/3

2,5x-2 - 4-0,75x > x+ 1
2,5x-0,75x-x > 1+2+4
0,75x > 7 |:0,75
x > 9 2/3
x ∈ (9 2/3; + ∞)

3-(x-2)²≤-4(1+x)+(√3-x)(x+√3)
3-x²-4x+4 ≤ -4-4x+(√3-x)(√3+x) ((√3-x)(√3+x) = (√3-x)(x+√3)) dodawanie jest przemienne. zamieniasz tak żeby był wzór skróconego mnożenia
3-x²-4x+4 ≤ -4-4x+(√3)²-x² (x² się skrócą, (√3)²=3
3+4+4 ≤ 4x - 4x
11 ≤ 0x yy. nierówność sprzeczna
1 5 1